Inner product inequalities with applications - Sababheh, Mohammad; Moradi, Hamid Reza; Sahoo, Satyajit (Linear & multilinear algebra, 2025)
In this paper, we show some inner product inequalities, which can be considered of Cauchy-Schwarz and Buzano type inequalities for Hilbert space operators. This will lead to several applications that include a new equivalent statement to the fact that an operator matrix is positive and new upper bounds for the numerical radius.